The present-time Milky Way stellar Metallicity Gradient. Issue Volume 14:Issue A30(2018) (August 2018) - Inno, Laura
Abstract: The present-time Milky Way (MW) radial metallicity gradient is a prime observable for galaxy evolution studies. Yet, a large diversity of measured gradients can be found in the literature, with values ranging from -0.01 to -0.09 dex kpc −1, depending on the tracers used. In order to understand if this diversity comes from Galactic evolution processes or observational biases, stellar probes uniformly distributed across the disc and with accurately known ages and distances are needed. Classical Cepheids fulfil all these requirements and have been used to measure accurate abundance gradients in the MW. Here, I summarise some of the recent results based on Cepheids and on other stellar probes of similar age, and briefly discuss their implication for Galactic evolution.